KAJIAN SEBARAN POTENSI EKONOMI SUMBER DAYA - Latif Sahubawa Nurul Khakim Musrowati Lasindrang (Universitas Gadjah Mada, 2015)
The objectives of research is to identify and inventory the economic potential of marine resources (fisheries and environmental services/beach tourism) and competitive commodity in the South Coast of DIY Province for investment purposes. The research method used is: a survey, the travel cost, the willingness to pay and analysis of competitive commodities. South Coast region of DIY Province which have valuable marine resources are economically important: Kulon Progo Regency (Congot and Galagah-Karangwuni Beach); Bantul (Pandansimo, Kuwaru, Depok and Parangtritis Beach); Gunungkidul (Sadeng, Wediombo, Siung, Sundak/Indrayanti, Drini, Baron, Ngerenehan, Gesing and Purwosari). The economic value of the resources of each coastal region as follows: (1) Kulon Progo Regency (fisheries = 519.817 IDR. billion and beach tourism = 0.608 IDR. billion, total 520.425 IDR. billion); (2) Bantul (fisheries = 121.455 IDR. billion and beach tourism = 2.961 IDR. billion: total 124.416 IDR. billion); (3) Gunung (fisheries = 63.957 IDR. billion and beach tourism = 6.803 IDR. billion; total 70.244 IDR. billion). The total economic value of marine resources of the South Coast of DIY Province DIY is 715.085 IDR. billion. Competitive commodity marine resources in Kulon Progo Regency Beach and Bantul is vanamme shrimp while in Gunungkidul are tuna, skipjack, tongkol, marlin, lemadang, layur, snapper, manyung and lobster.